Inconvenient Truths: Framing an Architectural History for Cold War Australia. Issue 2 (4th May 2021) - Goad, Philip
ABSTRACT: To date, Australia's architectural histories have been silent on the Cold War politics of post-war modernism. For the most part, historians have documented production without considering the broader geo-political moment in which the nation found itself after World War II. Recent transnational architectural histories focus on relationships that the United States and the former USSR forged between themselves and individually with other countries. In so doing, canonical accounts of post-war modernism have been brought into question and architectural practice implicated in broader global shifts of power, economy, and control. Some historians have concentrated on transatlantic connections, others have drawn peripheral modernisms into relief as a series of successive colonial modernisms. This paper explores aspects of Australia's post-war architectural production that might be regarded as inconvenient truths and implicated in a larger strategic geo-political and economic project. It suggests that the Cold War drew a net across Australia's entire landscape – urban and remote, seen and unseen. Australia was a willing collaborator. Under the auspices of post-war recovery and with a new-found purpose in the region, projects of extraction, energy, defence, and diplomacy 'rebuilt' the nation with a labour force contingent on migration - and architectural modernism was intrinsic to that project.